Quantifying Contributions of Magnetic Inclusions Within Silicates to Marine Sediments: A Dissolution Approach to Isolating Volcanic Signals for Improved Paleoenvironmental Reconstruction. Issue 10 (29th September 2021) - Jiang, X. D.; Zhao, X. Y.; Zhao, X.; Jiang, Z. X.; Chou, Y. M.; Zhang, T. W.; Yang, X. Q.; Liu, Q. S.
Abstract: Silicate‐hosted magnetic inclusions are a widespread fine grained magnetic component in marine sediments. However, their paleomagnetic and paleoenvironmental significance remains elusive as they are often overshadowed by unprotected detrital and biogenic magnetic components. We developed a protocol to extract silicate inclusions from sediments sampled from the central Pacific and the Okhotsk Sea. Our results show that the threshold condition (hydrochloric acid 10 mol/L with a reaction time of 24 h) can efficiently remove biogenic and unprotected magnetic phases and preserve silicate hosted magnetic inclusions that manifest a wide coercivity spectrum ranging between 10 and 300 mT with a median coercivity of ∼100 mT based on systematic rock magnetic analyses. This approach was applied to the Okhotsk Sea sediments, whose magnetic phases are dominantly derived from surrounding volcanic formations, spanning the last interglacial period. The residues after dissolution present a similar temporal variation compared to the bulk magnetic signal despite significant drops in amplitude. This suggests that the preserved signals of silicate inclusions can qualitatively represent the volcanic component. We suggest that when applied to sediments with complex magnetic components, this approach has the potential to extract volcanic components for paleoenvironmental reconstructions. Plain Language Summary: Magnetic mineral inclusions within silicates are an important magnetic component in marine sediments that can record long‐term paleomagnetic and paleoenvironmental information. However, it remains difficult to quantify their contribution due to the mixed magnetic properties in marine sediments including biogenic and detrital magnetic minerals with diverse grain sizes. We carried out systematic magnetic measurements to trace the dissolution processes of magnetic particles in sediments from the central Pacific Ocean and Okhotsk Sea and found the conditions (hydrochloric acid 10 mol/L with 24 h reaction time) that can efficiently remove biogenic and detrital magnetite leaving silicates that host magnetic inclusions. The preserved signals of silicate inclusions can qualitatively represent the volcanic component in marine sediments. We apply this approach to the central Okhotsk Sea sediments spanning the last interglacial period to demonstrate its potential for paleoenvironment reconstruction. Key Points: Dissolution behavior of unprotected magnetic particles follows the sequence from superparamagnetic particles, finer grains, and to coarser grains Magnetic inclusions within silicates are characterized of broad coercivity distribution of 10–300 mT Magnetic residues after dissolution contain dominantly volcanic components in marine environment